(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with the current value of short-term investments, and their way of analyzing and determining the price. At the present time, each household is estimated as the present valueis taken into account short-term financing and investment, analyzes the results of market conditions and changes that make it possible to predict the market value. During the execution of the investment project, discusses the changes in the present value of the shares. Due to changes in commodity prices, the depreciation of investments may occur, this is shown to prevent financial project. In investment projects in connection with the overvaluation of long-term financial investments particularly funding stops. In the course of financing the investment amounts, you must stop in the applicable measures that do not depreciate. If the rate of your income increase, it is necessary to consider the long-term financial investment.